A Randomized Study to Evaluate the Efficacy and Adverse Effects of Cryotherapy Combined with Intralesional Steroids, Intralesional Bleomycin Combined with Steroids and Fractional CO2 Laser in Keloids - P Sravya Krishna; K.V.T. Gopal; K Ananditha; V Sai Teja Reddy; T Narayana Rao (Indian Dermatology Online Journal)
Background: Despite the availability of various treatment modalities, the treatment of keloids is often incomplete, with a high recurrence rate. The present study was undertaken to assess the efficacy and safety of cryotherapy combined with intralesional steroid injections (Cy + ILS), intralesional combined bleomycin and steroids (ILB + S), and fractional carbon dioxide laser (Fr CO2) in keloid management. Patients and Methods: Ninety cases with keloids were enrolled and randomly divided into three groups of 30 patients each. The baseline severity of keloids was graded using the Vancouver scar scale (VSS) and high-frequency ultrasonography (HFUS). Group A, B, and C patients were treated with Cy + ILS, ILB + S, and Fr CO2, respectively for four sittings at 4-week intervals. Improvement in VSS score was calculated after 4, 8, 12, and 16 weeks, and with HFUS after 16 weeks. At each visit, adverse effects, if any, were noted. Statistical analysis was done using Chi-square test and ANOVA. Results: At the end of 16 weeks, the reductions in VSS in Cy + ILS, ILB + S, and Fr CO2 groups were 5.12 (60.09%), 5.84 (69.30%), and 3.06 (38.3%), respectively (P = 0.00). The difference in mean VSS reduction after 16 weeks between ILB + S and Cy + ILS was not significant (P = 0.28), whereas ILB + S and Cy + ILS were more efficacious than Fr CO2 (P = 0.01 and P = 0.02, respectively). The incidence of adverse effects was comparable between ILB + S and Fr CO2 (P = 0.11) but higher with Cy + ILS (P = 0.04). Limitations: Small sample size, non-blinded design, and short follow-up period. Conclusion: ILB + S may be considered as the first-line treatment option for keloids in view of its satisfactory efficacy, and excellent safety profile.